P645 Pharmacokinetics and immunogenicity of Infliximab biosimilar in inflammatory bowel disease patients. (25th January 2019) - Guardiola, J; Rodriguez Alonso, L; Padullés, N; Santacana, E; Serra, K; Padulles, A; Ruiz-Cerulla, A; Gilabert, P; Arajol, C; Ibañez-Sanz, G; Camps, B; Colom, H; et al.
Abstract: Background: Infliximab biosimilar (IFXbios) was the first monoclonal antibody approved by the European Medicines Agency (EMA) in 2013. Both reference IFX (IFXref) and IFXbios are approved for the treatment of eight immune-mediated inflammatory diseases including inflammatory bowel diseases (IBD). The aim of the present study was to compare real-life pharmacokinetics (PK) and the immunogenicity of IFXbios with IFXref in IBD patients. Methods: This is a retrospective comparative study from a prospectively maintained data base. Adult patients with IBD who received IFX between January 2014 and February 2018 were included. The primary endpoints were IFX trough concentrations (Cmin) and AUC at steady state. Secondary endpoints included: (1) Clearance (CL), (2) volume of distribution (Vc), (3) elimination rate (K10), and (4) half-life (t1/2). Safety assessment included the proportion of patients with anti-IFX antibodies (ATI). PK parameters and AUC were estimated by implementing a previously published population PK model using the software NONMEM® ver 7.4. We measured Cmin IFX and ATI using a commercially available validated enzyme-linked immunosorbent assay (ELISA) kit (Promonitor®). All data were analysed using software R (R Core Team 2017). Results: We included 73 patients (55 Crohn's disease, 18 ulcerative colitis). Fifty patients were on IFXref and 23 were on IFXbios. The majority (74%) received concomitant immunomodulator. Mean serum albumin concentration (SAC) was 4.38 g/dl (SD 0.42) and mean weigth was 69.53 kg (SD 15.39). The primary PK end points were shown to be similar among the two IFX formulations. IFXbios Cmin was 4.26 mg/l (SD 3.37), similar to IFXref Cmin (3.24 mg/l [SD 3.24]; p = 0.6668). There were no differences in AUC values between both IFXbios and IFXref. All secondary PK endpoints were also similar among the two treatment groups. The mean CL, Vc, K10, and t1/2 for IFXbios and IFXref were highly similar. PK characteristics of enrolled patients are in Table 1. Finally, a similar proportion of patients (8% in the IFXbios group and 6% in the IFXref group) developed ATI. Conclusions: Comparison between IFXbios and IFXref showed high similarity in the mean Cmin. The mean values of PK parameters (AUC, CL, Vc, Kel, and t 1/2 ) were comparable between treatment groups. The study also showed similar rate of ATI formation in patients on IFXbios and IFXref.